The Importance of ncRNAs as Epigenetic Mechanisms in Phenotypic Variation and Organic Evolution - Frías-Lasserre, Daniel; Villagra, Cristian A. (Frontiers in Microbiology, 2017)
Abstract Neo-Darwinian explanations of organic evolution have rested upon mutation as the principal factor originating evolutionary novelty. Mechanistic characterizations have been also biased by the classic dogma of molecular biology, where only proteins regulated gene expression. Together with it the rearrangement of genetic information, in terms of genes and chromosomes, was considered the cornerstone of evolution at level of natural populations. This predominant view excluded both alternative explanations as well as phenomenologies that do not fitted to its paradigm. With the discovery of non-coding RNAs (ncRNAs) and their role in the control of genetic expression new mechanisms aroused providing heuristic power to complementary explanations to evolutionary processes overwhelmed by mainstream genocentric views. Viruses, epimutation, paramutation, splicing and RNA editing have been revealed paramount functions in genetics variation, phenotypic plasticity and diversity. In this article a review is made about how current epigenetic advances on ncRNAs has changed the vision about the mechanisms that generate variation and how the organism-environment interaction can no longer be underestimated as drivers of organic evolution and is now part of the transgenerational inheritance and evolution of species. Key words: non-codingRNAs, phenotypic plasticity , biodiversity, adaptation, evolution